# Yahoo Web Search

related to K.C

1. Sort by

1. ### Mapping Notation - what if the k value is a fraction?

... graph:      af[k({x/k+d}-d)]+c = af[k(x/k)]+c = af[x]+c = {ay+c} ---- So, in your case, you need to use "+50...

4 Answers · Science & Mathematics · 19/07/2011

...where c is the constant of integration. T(t) = [r*t - r/k + H*β/k + c*exp(-k*t)] Plugging in the values for this problem: r = -2 deg/hr...

2 Answers · Science & Mathematics · 28/03/2010

3. ### Differential equation (Newtons law Of Cooling)?

...where c is the constant of integration. T(t) = [r*t - r/k + H*β/k + c*exp(-k*t)] Plugging in the values for this problem: r = -2 deg/hr...

2 Answers · Science & Mathematics · 28/03/2010

4. ### hard math question! help needed please!?

rate of kayak = k rate of current = c k + c = 26 k - c = 6 2k = 32 k = 16 --> c = 10

1 Answers · Science & Mathematics · 23/11/2010

5. ### Math Question: Combinations ?

a. total ways - ways with no women = 17c6 - 8c6 = 12348 <------ b. sum C(9,k)*C(8,6- k), k = 4 to 6 = 4620 <------ c. answer to (a) - 9c6 = 12,264 <-------

1 Answers · Science & Mathematics · 01/02/2014

6. ### CAN SOMEONE HELP ME ASAP (k+2)x^2-kx-2=0?

ax^2 + bx +c = 0 the discriminant is b^2 - 4ac a = k + 2 b = -k c = -2 (-k)^2 - 4(k + 2) * -2 >= 0 k^2 + 8k + 16 >= 0 (k + 4)^2 >= 0 k + 4 >=0 k >= -4 for real roots

2 Answers · Science & Mathematics · 28/09/2014

... that at least 1 boy, 1 girl need to be chosen, sum C(14,k)*C(9,k), k = 1 to 9 = 817,189 <------- either the q or ans ...

1 Answers · Science & Mathematics · 10/03/2013

...kt) you have decay so C=e^(-kt) fits. C'=-k*e^(-kt)=-k*C also fits. now to find k: 1/2=e^(-k*5545) ln(1/2)=-k*5545 -ln(2)=-k...

1 Answers · Science & Mathematics · 24/10/2011

9. ### 13 cards dealt. Probability of x aces and y clubs?

..., 0 to 1, k = non-ace clubs, 0 to 12 to get the relation P(i,j,k) = C(4,i+j)*C(12,k)*C(39,13-i-j-k)/C(52,13) i = 0 to 3, j...

1 Answers · Science & Mathematics · 31/03/2013

10. ### Writing an equation given asymptote and y-intercept?

...1, then kx - c = 0 for x = -1. This gives: k(-1) - c = 0 ==> -k - c = 0 ==> k + c = 0 ==> k = -c Since the y-intercept occurs at...

1 Answers · Science & Mathematics · 27/10/2009